2015
DOI: 10.1002/term.1989
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid scaffolds based on PLGA and silk for bone tissue engineering

Abstract: Porous silk scaffolds, which are considered to be natural polymers, cannot be used alone because they have a long degradation rate, which makes it difficult for them to be replaced by the surrounding tissue. Scaffolds composed of synthetic polymers, such as PLGA, have a short degradation rate, lack hydrophilicity and their release of toxic by-products makes them difficult to use. The present investigations aimed to study hybrid scaffolds fabricated from PLGA, silk and hydroxyapatite nanoparticles (Hap NPs) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 38 publications
1
45
0
2
Order By: Relevance
“…Sheik et al recently presented a novel PLGA/silk hybrid scaffold for bone tissue engineering applications in which the degradation rate of PLGA was combined with the hydrophilic silk polymer, as well as hydroxyapatite nanoparticles to further improve biocompatibility, and effectiveness was evaluated both in vitro and in vivo [183]. Variable-pressure field emission scanning electron microscopy (VP-FE-SEM) was used to demonstrate the porous nature of the scaffold, and contact angle measurements demonstrated that the silk component added further hydrophilicity to the scaffold.…”
Section: Applicationsmentioning
confidence: 99%
“…Sheik et al recently presented a novel PLGA/silk hybrid scaffold for bone tissue engineering applications in which the degradation rate of PLGA was combined with the hydrophilic silk polymer, as well as hydroxyapatite nanoparticles to further improve biocompatibility, and effectiveness was evaluated both in vitro and in vivo [183]. Variable-pressure field emission scanning electron microscopy (VP-FE-SEM) was used to demonstrate the porous nature of the scaffold, and contact angle measurements demonstrated that the silk component added further hydrophilicity to the scaffold.…”
Section: Applicationsmentioning
confidence: 99%
“…Fifteen male Sprague-Dawley rats were housed in separate cages with free access to laboratory rodent food and water under standardized air and light conditions at a constant temperature of 22 • C with a 12-h light/day cycle. Scaffolds that were 0.5 cm thick and cut into 3-mm diameter disks [29] using a tissue punch were incubated with hMSC for two weeks in an osteogenic medium, and each scaffold was then implanted into a rat calvarium. Four weeks later, when transplant materials were placed at the surgical site and osteoblast cells were grown at the implant site, they were observed by micro-CT (Micro CAT II; Siemens Medical Solutions).…”
Section: Animal Studymentioning
confidence: 99%
“…Synthetic scaffolds can be created with a variety of programmable features (i.e., porosity, pore size, degradation rate, and mechanical properties) that can be tailored to intended application sites. 27-31 However, polymers generally have a lower modulus than either metals or ceramics, 32 and thus have been limited in application to areas of low mechanical stress. 33 Given the need to precisely design bone tissue engineering scaffold properties, including morphology, resorption rate, osteoconductivity, and osteoinduction, attention has increasingly focused on the development of composites to tune these properties.…”
Section: Introductionmentioning
confidence: 99%